Nature+ Quantitative Baseline Household & Worker Survey, Kenya - International Food Policy Research Institute; Kula Vyema Centre (International Food Policy Research Institute, 2024)
In 2023, the Nature Positive Solutions (Nature+) baseline survey was conducted in Kenya, focusing on the Counties of Kisumu, Vihiga, and Kajiado. The study aimed to describe the socio-economic conditions and agricultural systems in these areas, providing a baseline assessment to inform ongoing Nature+ interventions. The survey covered 1,502 smallholder farmer households (752 treated and 750 control) across 25 villages. Data collection employed a two-stage sampling technique and assessed various variables, including socio-economic characteristics, agricultural practices, land use, nutrition, and adoption of Nature+ practices. This data will support the evaluation of Nature+'s impacts on inclusion, poverty reduction, food security, livelihoods, and environmental sustainability. Additionally, the survey included interviews with 1056 workers, covering socio-demographic characteristics, contract types, forced labor, harassment, workplace health and safety, wages, and overtime. All monetary variables are expressed in Kenyan Shilling (KSH).